Gone with the Wind [videorecording (DVD)] - Steiner, Max, 1888-1971; Mitchell, Margaret, 1900-1949 (Distributed by Warner Home Video, 2009)
Feature film: Focuses on the life and loves of the beautiful and selfish Scarlett O'Hara. The story begins on the O'Haras' Georgia plantation of Tara in antebellum days and moves through the Civil War and Reconstruction. This sweeping Civil War-era drama romance won an impressive 10 Academy Awards, and its immortal characters Scarlett, Rhett, Ashley, Melanie, Mammy and Prissy populate an epic story of enduring appeal across generations.